The Development of a Laundry Location Tracking Application Model Based on Artificial Intelligence and Mobile Computing - Muhammad Chaizir; Dahlan Abdullah; Muhammad Daud (Malikussaleh University, Aceh, Indonesia, 2023)
There is a lack of information systems that can facilitate the laundry business in reaching the market, so an application is needed to provide information to be known by many people in the city of Banda Aceh. One is by delivering information using the nearest laundry location search application. With the help of the internet and smartphones, it can make it easier for people to find the nearest laundry. The researcher is interested in designing a smartphone application to provide information on the nearest laundry. This study aims to create information media to develop an artificial intelligence-based laundry location search application model and a laundry location search application model with mobile Computing in Banda Aceh. The stages of this research are field observation, application design and design, application trials, research implementation permits, research data collection, and analysis of research results. The research implementation is located in the city of Banda Aceh. This research method is included in the Research and Development (RD) development category. The data collection used is as follows: notes on the results of interviews, field observations, and data related to informants. The results of this study are in the form of an application that provides information on the location of the nearest laundry from a distance of the user automatically when the application is run, and the user can search for the lowest price, 4+ star branches, and laundries that provide Pickup services.